2017
DOI: 10.1016/j.tube.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Green Fluorescent Protein as a protein localization and topological reporter in mycobacteria

Abstract: The cell envelope-associated proteins of Mycobacterium species play critical functions in the physiology and pathogenicity of these microorganisms. Because the determination of their subcellular localization and transmembrane topology is often critical to the understanding of their function, we investigated whether the Green Fluorescent Protein (GFP) could be used as a reporter to probe protein localization and map the topology of inner membrane proteins directly in intact mycobacterial cells. To this end, two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Plasmids expressing PE fused at the C terminus with either the GFP or the alkaline phosphatase (PhoA) (Table S1) were introduced in the WT strain of M. smegmatis, and the GFP and PhoA activities were monitored to determine the subcellular localization of the reporter proteins. GFP exhibits fluorescence only when localized to the cytosolic compartment, whereas PhoA is only active inside the periplasmic space (15,16). Expression of PE-GFP or PE-PhoA in an M. smegmatis pE knockout mutant (PMM229) restored TPP production, indicating that the fusion proteins are correctly folded and display proper subcellular localization in bacteria (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Plasmids expressing PE fused at the C terminus with either the GFP or the alkaline phosphatase (PhoA) (Table S1) were introduced in the WT strain of M. smegmatis, and the GFP and PhoA activities were monitored to determine the subcellular localization of the reporter proteins. GFP exhibits fluorescence only when localized to the cytosolic compartment, whereas PhoA is only active inside the periplasmic space (15,16). Expression of PE-GFP or PE-PhoA in an M. smegmatis pE knockout mutant (PMM229) restored TPP production, indicating that the fusion proteins are correctly folded and display proper subcellular localization in bacteria (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…To go further, the dynamic location of LipG within living cells was investigated by using fluorescence microscopy [ 66 ]. Gene fusions between Rv0646c or MSMEG_1352 and the sfGFP gene encoding the sfGFP [ 67 ] were generated and used to transform M. smegmatis cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, bioinformatics analysis did not reveal the presence of any secretion signals or specific motifs, which may indicate that the protein is surface exposed. Herein, using different cell-fractionation approaches, we demonstrated that LipG MTB is associated with the membrane fraction [ 54 , 55 , 66 ], but not translocated across the cytoplasmic membrane and remains a cytoplasmic protein which is mainly peripheral ( Figure 4 ). It has been described that such peripheral proteins require either a lipophilic attachment (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Among other applications, these FPs have been used in biosensors systems to monitor intracellular physiological parameters, like the pH, the oxygen level or the antioxidant activity (Potzkei et al, 2012; Crone et al, 2013; Germond et al, 2016). They are also useful as reporters of gene expression and transcription regulation (Chalfie et al, 1994; Webb et al, 1995; Ruiz-Cruz et al, 2010; Uliczka et al, 2011; Mohedano et al, 2014), or as biomarkers for imaging the subcellular location of fusion proteins and their targets (Webb et al, 1995; Phillips, 2001; Belardinelli and Jackson, 2017; Kapanidis et al, 2018), for direct detection and quantification of plasmid conjugation and plasmid loss (Nancharaiah et al, 2003; Sørensen et al, 2003; Bahl et al, 2004; Karimi et al, 2016), and for tracking the bacterial cells in in vivo and in vitro competition and interactomic studies (Singer et al, 2010; Campbell-Valois and Sansonetti, 2014; Jarchum, 2015; Russo et al, 2015). Imaging using these FPs as biomarkers is especially useful in living cells because is a non-destructive and minimally invasive method that does not require exogenously added substrates or cofactors (Chalfie et al, 1994).…”
Section: Introductionmentioning
confidence: 99%